HER2 Status in RAS and BRAF Wild-Type Metastatic Colorectal Cancer: A Portuguese Study - Fraga, Teresa (2023)
Introduction: Colorectal cancer (CRC) is the second-most deadly cancer worldwide. However, there remains a scarcity of precision treatments available for this type of cancer. Amplification or overexpression of human epidermal growth factor receptor 2 (HER2+) is a well-established therapeutic target in gastric and breast cancer. HER2 is positive in approximately 5% of CRC cases and has been implicated in resistance to therapy with anti-epidermal growth factor receptor antibodies. The aim of this study was to evaluate HER2 status in RAS and BRAF wild-type metastatic CRC (mCRC) and its correlation with survival outcomes. Materials and methods: A single-center retrospective analysis of RAS and BRAF wild-type mCRC patients undergoing systemic treatment was conducted from July 2014 to September 2020. Tissue HER2 status was determined by immunohistochemistry (IHC) and/or ﬂuorescence in situ hybridization (FISH) and/or chromogenic in situ hybridization (CISH). HER2+ was deﬁned as IHC3 (+) or IHC2 (+) through FISH or CISH (+). Results: Fifty-nine patients were included. The median age of all the included patients was 64 years (33-82). Four patients had HER2+ tumors (7%). Four patients had HER2+ tumors (7%). The majority of HER2+ mCRC cases were males (n=3) and left-sided CRC (n=3). All patients received FOLFIRI plus cetuximab as ﬁrst-line treatment. At the median follow-up of 24.0 months, patients with HER2-negative mCRC presented with a median overall survival (mOS) of 39.4 months (95% conﬁdence interval (CI) 32.7-46.0) and the four patients with HER2+ mCRC had a mOS of 20.4 months (95% CI; 9.5-31.3; p=0.07). In HER2-negative patients, the median PFS (mPFS) was 11.3 months (95% CI; 9.2-13.4) vsHER2-positive patients with a mPFS of 10.9 months (95% CI; 1.3-20.4; p=0.47). Conclusions: To our knowledge, this is the ﬁrst study reporting HER2+ in mCRC patients in a Portuguese population and the HER2+ rate was consistent with previous studies. Our study suggests that HER2+ may potentially be a marker that is able to predict poor prognosis in RAS and BRAF wild-type mCRC.